Do spacing and self-testing predict learning outcomes?. (March 2021) - Rodriguez, Fernando; Kataoka, Sabrina; Janet Rivas, Mariela; Kadandale, Pavan; Nili, Amanda; Warschauer, Mark
Studies have demonstrated that utilizing spacing (spreading out study sessions at regular intervals) and self-testing strategies are optimal for learning. While some applied work has examined the relationship between these strategies on general academic achievement, there is still a need to explore how both spacing and self-testing are related to course-level learning outcomes. The goal of this study was to examine whether utilizing spacing and self-testing strategies was related to final course grade. Participants were asked to report the study strategies they utilized during the course. We found no relationship between using spacing strategies and final course grade. However, self-testing was significantly related to higher final course grades. The relationship between self-testing and final course grade remained significant even after accounting for demographic differences and prior academic achievement. Our results suggest that self-testing strategies can enhance learning even in a highly structured course.